From Early Christian Region to Later Byzantine Hinterland: New Byzantine Marbles in the Archaeological Museum Kütahya - Niewöhner, Philipp (Istanbuler Mitteilungen, 2024)
This paper presents four dozen Byzantine marble carvings that the Archaeological Museum Kütahya acquired during the last two decades, since the publication of the museum’s earlier holdings. The marbles include architectural sculpture, mostly from the Early Byzantine period, and liturgical furnishings, also from later Byzantine times. The find-spots range widely across the huge catchment area of the museum, but the city of Kütahya and the district of Altıntaş each stand out for a cluster of finds. The paper provides an art-historical analysis and observes that, while some Early Byzantine carvings apply super-regional forms that are also known from other parts of the Eastern Roman empire, others and in particular liturgical furnishings are specifically Anatolian and attest to early Christian regionalism. This appears to have increased in the 6th century, as super-regional forms became rare. After a collapse during the Invasion period, Middle Byzantine stonemasonry followed different trajectories, certainly due to a lack of a major regional workshop and possibly in response to a new, aristocratic clientele that was oriented directly towards Constantinople instead of any regional centre, thus turning the formerly self-dependent region into an extended hinterland of the capital city.